Dietary intake in cystic fibrosis and its role in glucose metabolism. Issue 8 (August 2020) - Armaghanian, Natasha; Atkinson, Fiona; Taylor, Nicole; Kench, Andrea; Brand-Miller, Jennie; Markovic, Tania; Steinbeck, Kate
Summary: Background: Dietary intervention in cystic fibrosis (CF) has historically focused on high-energy diets to address malnutrition, with little attention on diet quality. With increased survival, CF complications such as impaired glucose tolerance (IGT) and cystic fibrosis related diabetes (CFRD) have increased in prevalence. In the absence of consensus on the management of IGT, the role of dietary intake, specifically carbohydrate quality, requires consideration. Aims: The aims of this study were to: 1) determine nutritional quality of dietary intake at an adult CF clinic and compare this to the Australian Dietary Guidelines 2) explore relationships between dietary intake, including glycaemic index (GI) and glycaemic load (GL), and glucose response variables using continuous glucose monitoring (CGM). Methods: Adults attending a Sydney hospital were recruited to undergo CGM for five-seven days and record dietary intake using a food record over the CGM period. The relationship between variables of dietary intake, including GI and GL and variables of glycaemic response, including mean amplitude of glycaemic excursions (MAGE), percentage of time in hyperglycaemic and euglycaemic range, were determined. Results: Eighteen participants completed the study with 87 full days of dietary and CGM data. Dietary intake was higher than recommendations in the Australian Dietary Guidelines in relation to grains and protein foods and only slightly higher in saturated fat. Bivariate correlations showed dietary GI was significantly positively associated with percentage of time in hyperglycaemic range. Dietary GL was significantly associated with SD, MAGE and percentage of time in euglycaemic range on CGM. Results remained significant when controlled for energy intake in partial correlation analyses. Conclusions: This study suggests GI and GL may be important dietary factors influencing glucose metabolism in CF. Further studies exploring low GI or GL diets as a dietary intervention in CF are the next step.